Empirical insights into the effects of research-based teaching strategies in quantum education - Donhauser, Anna; Bitzenbauer, Philipp; Qerimi, Linda; Heusler, Stefan; Küchemann, Stefan; Kuhn, Jochen; Ubben, Malte S. (Physical Review Physics Education Research, 2024)
The present review intends to show the current state of teaching quantum-related content, to analyze and compare its learning efficiency, and to give a systemized overview of quantum-educational activities in the last years. We focus on teaching and learning elements, their innovative tools, and process-oriented studies that are empirically validated. In terms of content, we mainly concentrate on aspects of modern quantum technology. The final dataset for our analysis and synthesis included 50 studies published since 2017 and until the follow-up survey in February 2024. We have found that most of the teaching strategies described and investigated are in the field of quantum mechanics and are designed to provide an introduction to the rather broad and differentiated topic of quantum science. Studies specifically addressing mathematical concepts can exclusively be found for the target group of university students. Visualizing ideas or innovative social interventions to improve quantum learning is mainly found in schools while only a few approaches for further education show validated results. Tools most often examined in the studies reported were of digital nature, though some experiment-focused learning environments were also evaluated.
CRIS-Team Scopus Importer:2025-02-04

Nanoscale analyses of Corynebacterium diphtheriae pili by atomic force microscopy - Rheinlaender, Johannes; Gräbner, Anna; Ott, Lisa; Burkovski, Andreas; Schäffer, Tilman (European Biophysics Journal, 2012)

Quantitative analysis of a wind energy conversion model - Zucker, Florian; Strunz, Andreas; Gräbner, Anna; Meyn, Jan-Peter (European Journal of Physics, 2015)
A rotor of 12 cm diameter is attached to a precision electric motor, used as a generator, to make a model wind turbine. Output power of the generator is measured in a wind tunnel with up to 15 m s-1 air velocity. The maximum power is 3.4 W, the power conversion factor from kinetic to electric energy is cp = 0.15. The v3 power law is confirmed. The model illustrates several technically important features of industrial wind turbines quantitatively.
UnivIS-Import:2015-04-14:Pub.2015.nat.dphy.PI.PDP.quanti
Keywords: Betz factor; demonstration experiment; model; renewable energy; wind energy; wind turbine